The Relationship Between Online Games Addiction As E-Sport To Sleep Quality Of Students Of SMP Negeri 1 Harau District: Hubungan Adiksi Games Online Sebagai E-Sport Terhadap Kualitas Tidur Siswa SMP Negeri 1 Kecamatan Harau - Aldi, Aldiansyah Dwi Putra; Muhammad Sazeli Rifki; wilda welis; Liza (Jurnal IKEOR, 2025)
The phenomenon of e-sport in Indonesia, in recent years, is booming and growing rapidly. Initially known as a recreational sport and now it has also become an achievement sport within its scope in sports according to Law of the Republic of Indonesia Number 3 of 2005 concerning the National Sports System. This phenomenon, for the adolescent age group is classified as more vulnerable to addiction to online games as an e-sport category. It is a problem for teenagers today, because they tend to overuse and spend time sitting in front of computer screens and mobile phones to play games so they forget to rest. Even though teenagers really need energy for daily activities, the best solution to rest is to sleep. Sleep is a universal activity consisting of a complex combination of physiological and behavioral processes producing a sense of freshness and well-being upon waking, ensuring that bodily functions are restored to optimal levels of functioning and alertness throughout the day. This research aims to determine whether there is a relationship between addiction to online games as e-sports and sleep quality of SMP Negeri 1 students in Harau District. This study used quantitative methods. The respondents in this study were 88 students of SMP Negeri 1 Harau District. Respondent selection uses purposive sampling techniques, namely by setting certain criteria as research samples. Data processing uses Pearson Product Moment correlation to prove the hypothesis. From the results of the study, it was found that the value of sig (2-tailed) was 0.00. This means that 0.00 < 0.05 then HO is rejected and Ha is accepted, so that the results are obtained that there is a significant strong relationship between online games addiction as e-sports to the sleep quality of SMP Negeri 1 Harau District students.